Correction of shear lag warping function of steel bottom – Corrugated steel web box girder. (March 2022) - Gong, Baojia; Liu, Shizhong; Mao, Yana; Qin, Aoao; Cai, Minghao
Abstract: To clarify the shear lag effect of the cross-section of steel bottom – corrugated steel web box girder, this study investigated the effect of replacing the concrete floor with a steel bottom on the additional warping displacement of the steel-concrete cross-section based on the energy variation principles of the cosine function method. Two methods are used to derive the maximum shear angle difference function of each member. Firstly, considering the influence of different material modulus and geometric size on the composite section of box girder, the warpage function is modified. On the other hand, the maximum angle difference function of each member on the composite section is assumed, and its expression is derived by using the matrix eigenvalue method. Refer to bridges under construction, a 6 m scale model beam is made and designed as the single box double chamber steel bottom - corrugated steel web box girder. By comparing the General beam theory, finite element method (FEM), Model beam test value and the correction method in this paper, the validity of this theory is verified.